WAVE2 2020 Pre-Text Elements and Committees - Gomes, Alex Sandro; Moreira, Fernando Joaquim Lopes; Primo, Tiago Thompsen (Anais do Workshop on Advanced Virtual Environments and Education (WAVE); 2020: Anais do III Workshop on Advanced Virtual Environments and Education, 2020)
Pre-textual elements and committees of WAVE 2 2020.